2001
DOI: 10.1080/019021401459770
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Functional Differences Between Rat Alveolar, Pleural, and Peritoneal Macrophages

Abstract: Tissue macrophages (M phi) play a central and essential role in modulating the initiation and perpetuation of the inflammatory response. Phenotypical and functional differences among alveolar M phi (AM) and peritoneal M phi (PM) have been reported, but less is known about pleural M phi (PLM) and their ability and capacity to release biologically active substances. Therefore, the aim of this study was to determine the production of superoxide anion, nitric oxide (NO), and tumor necrosis factor alpha (TNF-alpha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…The differential expression of cytokines between alveolar and peritoneal macrophages might be explained by different biological responses of two different cell populations (13,48). Salez et al (48) demonstrated that differentiation of mononuclear cells depends on the tissue environment: for example, the pulmonary environment allows alveolar macrophages to have different functions from peritoneal macrophages even though they derive from the same population of circulating monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The differential expression of cytokines between alveolar and peritoneal macrophages might be explained by different biological responses of two different cell populations (13,48). Salez et al (48) demonstrated that differentiation of mononuclear cells depends on the tissue environment: for example, the pulmonary environment allows alveolar macrophages to have different functions from peritoneal macrophages even though they derive from the same population of circulating monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Their functional and phenotypic characteristics depend on their location and are determined by the surrounding micromilieu. Several animal experiments have compared the phenotype and inflammatory capacity of pleural mu to peritoneal and alveolar mu [6,7]. Moreover, in a recent study, using selective mu depletion in mice, their functional importance for the initiation of an inflammatory reaction in the pleural cavity has been shown [8].…”
Section: Introductionmentioning
confidence: 98%
“…Findings of previous studies have relied upon nonalveolar and nonhuman macrophages, and the significance of some findings is obscured by different responses of alveolar macrophages compared with blood macrophages. For example, studies have shown alveolar macrophages to be selectively up-regulated by cytokines and LPS compared with same-donor blood monocytes (10,11). However, the role of antigens of respiratory bacteria on this process has not been explored.…”
mentioning
confidence: 99%